Aquisição das líquidas por criança com síndrome de Down: um estudo longitudinal - Ferreira, Jóice de Oliveira (2021)
This research aims to monitor and describe the speech acquisition of a child with Down syndrome in a longitudinal study. Observe individual characteristics of language development, taking into account this very form of acquisition (SLOBIN, 2015). The focus of the research is the study of the acquisition of the liquid consonants /l, R, ʎ, ɾ/ in simple onset and in the Brazilian Portuguese tautosyllabic consonant clusters. According to Lamprecht (2004), liquids are the last sounds to be acquired and, due to their complexity, the child seeks to use repair strategies in order to reach the target language, that is, that of the adult. Knowing the complexity of its acquisition by children with typical speech, it is observed through this longitudinal case study, the acquisition of this class of sounds by a child with atypical speech (DS). The theoretical support is Exemplary Theory and Complex Adaptive Systems (CAS's). The Exemplars Theory is a use-based and multirepresentational model that argues that the speaker stores in his mind multiple examples for the same linguistic item, with the word being the object of analysis (PIERREHUMBERT, 2001). Complex Adaptive Systems argue that language is a complex, variable and non-linear adaptive system that is constantly changing over time (NASCIMENTO, 2011). The dynamic model, despite dealing with child development in general, contributes to the understanding of child language development. The relevance of the longitudinal study is also highlighted, which allows observing and reflecting on the comings and goings during the acquisition period (SCARPA, 2012). It is in the positive feedback that this path presents moments of discontinuity, modifying the initial state, generating an imbalance that will be recovered along the path, reaching stabilization in search of self-organization (OLIVEIRA, 2016). According to Paiva (2011), each individual adopts different strategies when faced with the same challenge. The exemplar model and the dynamic model have points in common, such as the importance of the role of frequency in the organization of the language and that grammar emerges from use based on non-linearity. Experience, in addition to affecting production, affects perception and storage of phonological items. Throughout the research, periodic recordings and speech notes were made, with the involvement of family members in everyday situations, spontaneously, in order not to interfere in the child's daily activities. We sought to analyze the data qualitatively, observing individual characteristics of the research subject. It was verified in the informant's data that the phonological acquisition takes place in a complex and variable way, with different paths to reach the same lexical structure, as postulated by the Exemplary and Complex Adaptive Systems Theory. It was also verified the importance of the longitudinal study to understand the variability and dynamics of phonological acquisition, making it possible to make reflections and raise hypotheses from the moments of comings and goings, continuities and discontinuities present in this path in the search for the adult target (self-organization).